A Study on Historical Fiction As Described In Salman Rushdie’S Novels: Unveiling the Power of Storytelling in Salman Rushdie's Historical Novels (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Post-colonial historiography and historical fiction havecome to share common concerns about representation with post-modem historic-graphicmet fiction where story telling along with revelation in their own narrativelybecomes a historical and political act. As Simon argues, post- colonial  writing becomes  one  of the  ways  of subverting  imperial  myths by 'foregrounding the fact that history is not a set of immovable pastachievements but a discourse, open  toreinterpretation.'